"Taught by reality": Brecht's Haltung and the profitable uses of a materialistic super-objective. Issue 2 (2nd July 2020) - Mirodan, Vladimir
ABSTRACT: Haltung (variously translated as attitude, stance, bearing, posture or demeanour) is as central to Brecht's approach as the concept of Super-Objective is to Stanislavsky's. For the actor seeking to draw on both traditions, dialectical tensions can arise between Haltung /Attitude (a sociological construct, essentially fluctuating and inconsistent) and Super-Objective (a psychological concept, fundamentally constant and stable). This paper proposes incorporating these apparently contradictory concepts into a unified working methodology for the actor. The paper starts by reviewing key theoretical pronouncements made by Brecht in relation to Haltung and describes an interesting extension of this concept in the practice of a contemporary theatre company. Brecht's views on personality and, by extension, of dramatic character, are reviewed and tested in the light of current perspectives in the psychology of individual difference. The paper goes on to examine the concept of Haltung in light of Stanislavsky's notion of "inner tone" and considers that current models of personality as well as the rehearsal practices of Brecht's main actors support a conflation of the notions of Haltung and Super-Objective, yet concludes that the adoption of a Haltung of necessity leads actors to selecting a certain type of Super-Objective and "inner tone", here defined as "realistic". Throughout, examples are offered using the records of Brecht's productions of Mother Courage and The Caucasian Chalk Circle . A final section illustrates how the working model proposed could be applied to an understanding of a character normally associated with the Stanislavskian tradition: Lopakhin in The Cherry Orchard .